Sclerotinia wilt of french bean - and N.P. DOHROO, S.K. GUPTA, K.R. SHYAM (Indian Phytopathology, 2002)
In August, 1994, Sclerotinia wilt of Phaseolus vulgaris was recorded in Himachal Pradesh, India. The causal organism was isolated and identified as S. sclerotiorum.